The International Economy and Economic Development - Джереффи, Гэри (Journal of Economic Sociology, 2010)
Here by the main part of the work is given. The paper goal is to provide the simplified review of the growing globalization of the economic activity as well as the interactions between changing characteristics of the world economy and economic development. The paper consists of several parts. Firstly the author describes the main historical periods of the international economy evolution. The key institutional characteristics of the international economy are analyzed on the basis of the example of five eras: early capitalism, capitalism of the free competition, imperialism, monopolistic capitalism and global capitalism. Secondly, the author describes the following approaches to the research of the economic internalization and its impact on the development: imperialism theories, economic theory of development, theory of dependence, theory of world system, discussions about the strategies of national development. Thirdly, the paper deals with the more detailed analysis of the contemporary development directions of the international economy. глобализация